PERANCANGAN SISTEM INFORMASI SECARA ONLINE PADA TOKO BUKU MULTIMEDIA BEKASI - , RENDY RIDIANTO JAUHARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Along with the rapid development of the technology, the development of the Internet is increasing. Nowadays the Internet is accessible by the public. Internet users can exchange information easily at the same time. The development of information technology has also touched the field of economics. So there was the term electronic commerce or e-commerce is currently growing. E-commerce services provide broad market opportunities for Internet users around the world. Mutimedia Bookstore is located in the City of Bekasi, East Jakarta is a store that provides a wide variety of books needed by the community. Due to lack of information and the lack of effective sales so that sales of products not optimal because it is difficult to reach customers who are out of town. Therefore we need a system that if it can run optimally. To overcome these problems, developed a system of e-commerce online bookstore. The e-commerce system that is used is one of the name-based web developer CMS (Content Management System) and is open source. In the online bookstore is equipped with features and stock information books, purchase books online, tracking purchase status and send a message to the admin.